(untitled) (Journal of the College of Basic Education, 2022)
Paper is one of the most important materials that show the possibility of a calligrapher and his ability to be creative. beauty and workmanship, and it is necessary to deal technically with that raw material, which in turn acts as a founding verb linear achievement in order to achieve technical diversifications when preparing them to reach intellectual and practical implications. Especially in the field of art apro. This art is not a traditional art, but rather an original art linked to Islamic roots that has its own distinctive style. And his own way, as he was associated with the arts of Arabic calligraphy, as gilding was associated with it.